1999
DOI: 10.1017/s0012162299000833
|View full text |Cite
|
Sign up to set email alerts
|

Head circumference in ELBW babies is associated with learning difficulties and cognition but not ADHD in the school-aged child

Abstract: This study examines whether a small head circumference (HC) and low head-circumference growth velocity (HGV) during the first year of life predict consequences at school age in learning, cognition, and concentration. A total of 124 extremely-low-birthweight (ELBW) infants (birthweight 500 to 999 g) born between 1977 and 1986 were eligible for follow-up at the corrected ages of 4, 8, and 12 months and 2, 4, and 6 years. Infants were categorized as having a small HC (< 3% or 3 to 10%) on the basis of the 1990 Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 31 publications
3
23
0
2
Order By: Relevance
“…This association became, however, non-significant after controlling pre- and neonatal covariates. Finally, Stathis et al [20] failed to find any significant associations among 87 extremely-low-birth weight born children between subnormal head circumference (comparison to norm z-scores) or head growth velocity from birth to 2 years and parent/teacher rated ADHD diagnoses at school-age. Because of differences in age of the samples and periods of growth, direct comparison of our results showing an association between a smaller head circumference throughout the period of growth from birth to 56 months with higher levels of ADHD symptoms at 56 months, with earlier findings is not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association became, however, non-significant after controlling pre- and neonatal covariates. Finally, Stathis et al [20] failed to find any significant associations among 87 extremely-low-birth weight born children between subnormal head circumference (comparison to norm z-scores) or head growth velocity from birth to 2 years and parent/teacher rated ADHD diagnoses at school-age. Because of differences in age of the samples and periods of growth, direct comparison of our results showing an association between a smaller head circumference throughout the period of growth from birth to 56 months with higher levels of ADHD symptoms at 56 months, with earlier findings is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, to our knowledge only two studies to date have addressed the role of physical growth in ADHD: the first compared growth of 48 boys with ADHD in relation to population norms and found a distinct suppression of growth in height from 9 to 14 years, earlier onset of adolescent growth spurt and a higher velocity of growth in that moment [15]. The second study showed in 87 extremely-low-birth-weight boys and girls that growth in head circumference between birth and two years did not predict parent/teacher-rated ADHD at school-age [20]. The current study will test if growth in height, weight, BMI and head circumference from birth up to five, 20, and 56 months of age is associated with parent-rated ADHD symptoms at 56 months.…”
Section: Introductionmentioning
confidence: 99%
“…French et al (1999) have reported a decrease in head circumference with exposure to increased number of antenatal glucocorticoid courses [161]. Further, small head circumference at birth and head circumference growth velocity during the first year of life have been strongly associated with learning difficulties and cognition in school aged children [167]. A recent report has demonstrated that individuals who had larger head circumference as adults gained significantly higher scores on intelligence tests and were less likely to show a decline in memory performance with age [166].…”
Section: Effect Of Fetal Glucocorticoid Exposure: Human Studiesmentioning
confidence: 99%
“…Although there is some indication that the associations may have been more pronounced for boys in the birth weight regression, further research is required to confirm sex differences. Poor infant health at birth, as measured by birth weight and head circumference, has been widely associated with poorer long-term outcomes such as latent health issues, lower educational attainment, and adverse labor market outcomes (Behrman and Rosenzweig 2004; Black et al 2007; Boardman et al 2002; Case et al 2005; Chatterji et al 2014; Currie and Hyson 1999; Gale et al 2004; Gross et al 1978, 1983; Stathis et al 1999). In particular, low birth weight and small head circumference have been associated with cognitive and neurological impairments and poorer health as adults (Behrman and Rosenzweig 2004).…”
Section: Discussionmentioning
confidence: 99%